The effect of radiation parameterization schemes on surface temperature in regional climate simulations over the MENA‐CORDEX domain. (22nd December 2016) - Zittis, G.; Hadjinicolaou, P.
ABSTRACT: We investigated the effect of radiation schemes on the performance of a climate version of the Weather, Research and Forecasting (CLWRF) model over a domain covering the Middle East and North Africa (MENA), so often called the Arab domain. The ability of the model to reproduce recent past climate conditions was tested with 30‐year simulations that cover the 1981–2010 period. The model was driven by the ERA‐Interim reanalyses at a horizontal resolution of 50 km. We explored the sensitivity of the model to the short‐ and long‐wave (LW) radiation parameterizations by testing the RRTMG and CAM3 schemes in order to optimize the model performance as a contribution to the MENA‐CORDEX initiative. The results have been compared with gridded surface observational data and satellite measurements for several variables, including mean, maximum and minimum 2‐m air temperature, total cloud cover and surface short‐ and LW radiation fluxes. The model is found to capture reasonably well the inter‐annual variability and the observed warming trends over the last three decades. Although we generally found that CAM3 driven simulations are relatively cooler than the RRTMG driven ones, each radiation scheme can give better results depending on the season, location and dominant land use type of each of the model's grid point. The largest discrepancies between these hindcast simulations are found over the desert part of the domain while they are found to closely agree over southern Europe.